STUDI POSKOLONIAL TERHADAP KAWASAN ALUN-ALUN JEMBER: USAHA MENGGALI POTENSI KOTA KREATIF - Y.A. Widriyakara; Anas Hidayat; Lucia Ina Trisjanti (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2016)
Title: Postcolonial Study towards Jember Alun-alun Area: Efforts to Explore the Potential of Creative City The Alun-alun is an important area in the city in Java, which has existed since pre-colonial era (can be traced back to the Majapahit era), which was later adapted creatively by the Dutch in colonial era to the post-independence of Indonesia. Studies on the Alun-alun is mostly done historically, symbolic or functional, whereas this study viewed from the perspective of postcolonial, that reverse point of view: from the square is considered passive and influenced, being square is active and can be aligned with the global trend. The research method is qualitative research, with a view creativity of Jember society in the process of changes. This study combines direct observation, observe documents and interview. Alun-alun became a media of